2011
DOI: 10.1002/jsfa.4718
|View full text |Cite
|
Sign up to set email alerts
|

Advanced preservation methods and nutrient retention in fruits and vegetables

Abstract: Despite the recommendations of international health organizations and scientific research carried out around the world, consumers do not take in sufficient quantities of healthy fruit and vegetable products. The use of new, 'advanced' preservation methods creates a unique opportunity for food manufacturers to retain nutrient content similar to that found in fresh fruits and vegetables. This review presents a summary of the published literature regarding the potential of high-pressure and microwave preservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(124 citation statements)
references
References 81 publications
0
120
1
3
Order By: Relevance
“…Regard to the phenolic content, both CPPs had a lower phenolic content (p < 0.05) compared to the phenolic content found in fresh carrot pomace (1505.35 ± 27.5 mg GAE/100g CPP obtained with microwaves and 1412.26 ± 6.36 mg GAE/100g CPP gotten with hot air vs. 1841.08 ± 40.14 mg GAE/100g fresh carrot pomace, Table 4). The reduction could be explained since phenols are extremely sensitive to thermal treats [32][33][34] however, the results obtained in the present work, showed that the microwave drying reduced the phenol loose in a 5% compared with the hot air drying.…”
Section: Phytochemical Content and Antioxidant Activitycontrasting
confidence: 50%
“…Regard to the phenolic content, both CPPs had a lower phenolic content (p < 0.05) compared to the phenolic content found in fresh carrot pomace (1505.35 ± 27.5 mg GAE/100g CPP obtained with microwaves and 1412.26 ± 6.36 mg GAE/100g CPP gotten with hot air vs. 1841.08 ± 40.14 mg GAE/100g fresh carrot pomace, Table 4). The reduction could be explained since phenols are extremely sensitive to thermal treats [32][33][34] however, the results obtained in the present work, showed that the microwave drying reduced the phenol loose in a 5% compared with the hot air drying.…”
Section: Phytochemical Content and Antioxidant Activitycontrasting
confidence: 50%
“…At the most general level, food can be degraded in three ways. First, even in the complete absence of bacteria or fungi, food may lose nutritional quality through a breakdown in structure due to a number of physical and chemical processes [10,16]. Second, microbial proliferation in food leads to losses of the nutrients and energy originally available to non-microbial competitors (e.g., humans) as these resources are diverted into the growth of indigestible bacteria [51,59,60].…”
Section: Summary Of Trends and Susceptibility Estimatesmentioning
confidence: 99%
“…ice crystal formation) and the associated rapid expansion and contraction of water can result in damage to cellular structures [10,86,87,170]. As a result of the degradation of cellular structures, freeze-thaw events can affect multiple aspects of food quality and several studies in applied food science have been conducted to understand the mechanisms behind these processes.…”
Section: Freeze-thaw Eventsmentioning
confidence: 99%
“…It was stated that dry weight content of vitamin C in strawberry and blackberry purées was signifi cantly higher in HPP--treated samples [Barrett & Lloyd, 2012]. It was reported that the level of retention of ascorbic acid in guava purée proceeded according to the following decreasing order: (400 MPa for 15 min) > (88-90 °C for 24 s) > (600 MPa for 15 min) [Yen & Lin, 1999].…”
Section: Hhpp Applications On Phenolic and Antioxidant Bioactives Of mentioning
confidence: 99%